Dataset of manually classified images obtained from a construction site - Montoya Matos, Israel Roger (2024)
In the present work the effect of alkali ions (Li, Na, K) and the combination of them on structural and spectroscopic properties of Nd3+ doped silicate glasses were systematically investigated. Results from infrared and Raman spectroscopy, as well as density and refractive index, were used to investigate the effect on the structural properties of the silicate glasses. Absorption and emission spectra of the glass samples were measured in the UV-VIS and NIR ranges. Relatively large, stimulated emission cross-section at 1.06 µm was obtained for samples containing a combination of alkali ions, especially with potassium. Moreover, the splitting induced by the Stark effect on the hypersensitive transition of Nd3+,4I9/2 ¿ 4G5/2, 2G7/2 was larger for the samples containing potassium, probably due to its larger ionic size. Judd-Ofelt theory was applied to evaluate the phenomenological intensity parameters O2, O4, O6, transition probabilities, radiative lifetimes and branching ratios related to Nd3+ ions, calculated from optical absorption and luminescence spectra and the results were compared to the values obtained for different Nd-doped glasses reported in the literature.